Digestibility of Calanus finmarchicus wax esters in Atlantic salmon (Salmo salar) freshwater presmolts and seawater postsmolts maintained at constant water temperature - Oxley, Anthony; Bogevik, Andre S; Henderson, R James; Waagbo, Rune; Tocher, Douglas R; Olsen, Rolf E (Aquaculture Nutrition, 2009)
Calanoid copepods are a rich source of n-3 highly unsaturated fatty acids (HUFA) for potential use in aquafeeds. However, as copepod oil is primarily composed of wax esters (WE), there are concerns over the efficiency of wax ester, versus triacylglycerol (TAG), digestion and utilisation in fish. As smoltification represents a period of major physiological adaptation, the present study examined the digestibility of a high wax ester diet (Calanus oil; 230 g kg-1 diet; 48% WE, 26% TAG), compared to a triacylglycerol diet (fish oil; 230 g kg-1 diet; 58% TAG), in Atlantic salmon freshwater pre-smolts and seawater post-smolts, of similar age (9 months) and weight (112 g and 141 g initial respectively), over a 98 day period at constant temperature and lighting regimes. Fish grew significantly better, and possessed lower feed conversion ratios (FCR), in seawater than freshwater. However, total lipid apparent digestibility coefficient (ADC) values were significantly lower in seawater fish, as were total fasted bile volumes. Dietary Calanus oil also had a significant effect, reducing growth and lipid ADC values in both freshwater and seawater groups. Post-smolts fed dietary Calanus oil had the poorest lipid ADC values and analysis of faecal lipid class composition revealed that 33% of remaining lipid was wax ester and 32% fatty alcohols. Dietary prevalent 22:1n-11 and 20:1n-9 fatty alcohols were particularly poorly utilised. A decrease in major bile acid, taurocholate, concentration was observed in the bile of dietary Calanus oil groups which could be related to the lower cholesterol content of the diet. It is suggested that, following smoltification and rapid growth in seawater, there is a lag phase in digestive function where bile production is not sufficient to emulsify and render wax esters available for hydrolytic action by luminal lipases. These effects appear to be related to the life stage of the fish and could also represent an upper limit of wax ester inclusion in diets.